Impact of Left Ventricular Diastolic Pressure Changes on Clinical Outcomes After Transcatheter Aortic Valve Replacement - Jiwon Seo; Ah‐Ram Kim; Iksung Cho; Chi Young Shim; Geu‐Ru Hong; Eui‐Young Choi; Se‐Joong Rim; Young‐Guk Ko; Myeong‐Ki Hong; Jae‐Kwan Song; Jong‐Won Ha (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Changes in left ventricular (LV) diastolic pressure after transcatheter aortic valve replacement (TAVR) or their relationship with subsequent outcomes remain poorly clarified. Accordingly, we aimed to assess the changes in invasively measured LV diastolic pressure and their relationship with long‐term outcomes in patients undergoing TAVR. Methods In total, 509 patients with severe aortic stenosis who underwent TAVR at 3 tertiary centers were retrospectively included and divided into 2 groups according to changes in LV pre‐A pressure after TAVR: Group 1, with no change or decrease in pre‐A pressure, and Group 2, presenting an increase in pre‐A pressure after TAVR. The primary outcome was a composite of all‐cause death and rehospitalization for heart failure. Results Group 1 included 39% (n=198) patients, and Group 2 had 61% (n=311) patients. More patients in Group 2 had diabetes, chronic kidney disease, and a larger aortic valve area than in Group 1. During the follow‐up period (median, 28 months), 122 primary outcomes were recorded. In Kaplan‐Meier analysis, the cumulative incidence of the primary outcome and all‐cause death was significantly lower in Group 1 than in Group 2. In multivariable Cox hazard models, Group 1 was independently associated with a favorable primary outcome (hazard ratio, 0.52 [95% CI, 0.34–0.80]; P=0.003). Conclusions Increase in LV pre‐A pressure after TAVR is common, and no change or decrease in LV pre‐A pressure after TAVR is independently associated with favorable outcomes. Changes in LV pre‐A pressure can help identify patient subsets who will maximally benefit from TAVR.